2023
DOI: 10.1021/acs.jpclett.2c03857
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Ultrafast Electron Dynamics in CuO Photocatalysts Probed by Surface Sensitive Femtosecond X-ray Absorption Near-Edge Structure Spectroscopy

Abstract: CuO is often employed as a photocathode for H2 evolution and CO2 reduction, but observed efficiency is still far below the theoretical limit. To bridge the gap requires understanding the CuO electronic structure; however, computational efforts lack consensus on the orbital character of the photoexcited electron. In this study, we measure the femtosecond XANES spectra of CuO at the Cu M2,3 and O L1 edges to track the element-specific dynamics of electrons and holes. Results show that photoexcitation represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Figures D, E, and F show XPS spectra of the three samples and provide information on the oxidation states of the Cu oxide samples. While UV–vis absorption and Raman spectroscopy probe the bulk films, XPS is a surface sensitive technique that primarily samples only the top ∼2 nm of the Cu oxide samples. , This value is comparable with the probe depth of XUV-RA measurements . Hence XPS measurements are helpful to understand the nature of the surface and characterize the defect, which influences the ultrafast surface dynamics observed by XUV-RA spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures D, E, and F show XPS spectra of the three samples and provide information on the oxidation states of the Cu oxide samples. While UV–vis absorption and Raman spectroscopy probe the bulk films, XPS is a surface sensitive technique that primarily samples only the top ∼2 nm of the Cu oxide samples. , This value is comparable with the probe depth of XUV-RA measurements . Hence XPS measurements are helpful to understand the nature of the surface and characterize the defect, which influences the ultrafast surface dynamics observed by XUV-RA spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…XUV-RA instrumentation and methodology have been previously described in detail in recent publications and a concise description is given in section 1 of Supporting Information. , To briefly explain, there are two types of XUV-RA experiments that are conducted, namely, static (i.e., ground state) and transient. Static Cu M 2,3 -edge spectra are measured based on the reflected XUV intensity from Cu oxide samples, referenced to TiO 2 , which has high XUV reflectivity and no resonant absorption features overlapping with Cu M 2,3 -edge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In a similar vein, Bandaranayake et al conducted femtosecond XANES spectroscopy on CuO, allowing them to monitor the element-specific dynamics of electrons and holes. 19 Xiong et al undertook a systematic screening of thermoelectric semiconductors, discerning their conduction types based on the energy positions of their band edges. 20 Additionally, some newly discovered band-edge electronic states, such as Urbach-edge, 21 have received widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…Slavney et al observed that defect-induced band-edge reconstruction enables the bismuth-halide double perovskite Cs 2 AgBiBr 6 to effectively absorb visible light . In a similar vein, Bandaranayake et al conducted femtosecond XANES spectroscopy on CuO, allowing them to monitor the element-specific dynamics of electrons and holes . Xiong et al undertook a systematic screening of thermoelectric semiconductors, discerning their conduction types based on the energy positions of their band edges .…”
Section: Introductionmentioning
confidence: 99%